Norepinephrine‐CREB1‐miR‐373 axis promotes progression of colon cancer. Issue 5 (13th March 2020) - Han, Jia; Jiang, Qiuyu; Ma, Ruili; Zhang, Huahua; Tong, Dongdong; Tang, Kaijie; Wang, Xiaofei; Ni, Lei; Miao, Jiyu; Duan, Baojun; Yang, Yang; Chen, Yanke; et al.
Abstract : The adrenergic system contributes to the stress‐induced onset and progression of cancer. Adrenergic fibers are the primary source of norepinephrine (NE). The underlying mechanisms involved in NE‐induced colon cancer remain to be understood. In this study, we describe the function and regulatory network of NE in the progression of colon cancer. We demonstrate that NE‐induced phosphorylation of cAMP response element‐binding protein 1 (CREB1) promotes proliferation, migration, and invasion of human colon cancer cells. The downstream effector of NE, CREB1, bound to the promoter of miR‐373 and transcriptionally activated its expression. miR‐373 expression was shown to be necessary for NE‐induced cell proliferation, invasion, and tumor growth. We confirmed that proliferation and invasion of colon cancer cells are regulated in vitro and in vivo by miR‐373 through targeting of the tumor suppressors TIMP2 and APC. Our data suggest that NE promotes colon cancer cell proliferation and metastasis by activating the CREB1–miR‐373 axis. The study of this novel signaling axis may provide mechanistic insights into the neural regulation of colon cancer and help in the design of future clinical studies on stress biology in colorectal cancer. Abstract : We propose a NE–CREB1–miR‐373 signaling axis in human colon cancer cells. NE promotes the progression of colon cancer via CREB1 activity‐dependent transcription, enhancing the expression of oncogenic miR‐373 and reducing the expression of the miR‐373 targets APC and TIMP2. This novel NE‐CREB1‐miR‐373 signaling axis may potentially serve as a new therapeutic target for colorectal cancer.